Higgsing M2 to D2 with gravity: N=6 chiral supergravity from topologically gauged ABJM theory - Chu, Xiaoyong; Nastase, Horatiu [UNESP]; Nilsson, Bengt E. W.; Papageorgakis, Constantinos (Springer, 2011)
We present the higgsing of three-dimensional N = 6 superconformal ABJM type theories coupled to conformal supergravity, so called topologically gauged ABJM theory, thus providing a gravitational extension of previous work on the relation between N M2 and N D2-branes. The resulting N = 6 supergravity theory appears at a chiral point similar to that of three-dimensional chiral gravity introduced recently by Li, Song and Strominger, but with the opposite sign for the Ricci scalar term in the lagrangian. We identify the supersymmetry in the broken phase as a particular linear combination of the supersymmetry and special conformal supersymmetry in the original topologically gauged ABJM theory. We also discuss the higgsing procedure in detail paying special attention to the role played by the U(1) factors in the original ABJM model and the U(1) introduced in the topological gauging.
Keywords: D-branes; Chern-Simons Theories; Supergravity Models; M-Theory